The clinical impact of donor-specific antibodies in heart transplantation - Barten, Markus Johannes; Schulz, Uwe; Beiras-Fernandez, Andres; Berchtold-Herz, Michael; Boeken, Udo; Garbade, Jens; Hirt, Stephan; Richter, Manfred; Ruhparwar, Arjang; Sandhaus, Tim; Schmitto, Jan Dieter; Schönrath, Felix; et al. (Transplantation reviews, 2018)
Donor-specific antibodies (DSA) are integral to the development of antibody-mediated rejection (AMR). Chronic AMR is associated with high mortality and an increased risk for cardiac allograft vasculopathy (CAV). Anti-donor HLA antibodies are present in 3-11% of patients at the time of heart transplantation (HTx), with de novo DSA (predominantly anti-HLA class II) developing post-transplant in 10-30% of patients. DSA are associated with lower graft and patient survival after HTx, with one study suggesting a three-fold increase in mortality in patients who develop de novo DSA (dnDSA). DSA against anti-HLA class II, notably DQ, are at particularly high risk for graft loss. Although detection of DSA is not a criterion for pathologic diagnosis of AMR, circulating DSA are found in almost all cases of AMR. MFI thresholds of ~5000 for DSA against class I antibodies, 2000 against class II antibodies, or an overall cut-off of 5−6000 for any DSA, have been suggested as being predictive for AMR. There is no firm consensus on pre-transplant strategies to treat HLA antibodies, or for the elimination of antibodies after diagnosis of AMR. Minimizing the risk of dnDSA is rational but data on risk factors in HTx are limited. The effect of different immunosuppressive regimens is largely unexplored in HTx, but studies in kidney transplantation emphasize the importance of adherence and maintaining adequate immunosuppression. One study has suggested a reduced risk for dnDSA with rabbit antithymocyte globulin induction. Management of DSA pre- and post-HTx varies but typically most centers rely on a plasmapheresis or immunoadsorption, with or without rituximab and/or intravenous immunoglobulin. Based on the literature and a multi-center survey, an algorithm for a suggested surveillance and therapeutic strategy is provided.